Hubungan Antara Penataan Situasi Belajar Siswa Dengan Hasil Belajar Akidah Akhlak Di Kelas V Mi Nurul Huda Kapongan Situbondo - Zainal Arifin (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2020)
The role of the teacher in classroom management is very important to create a quality learning atmosphere. In principle, the teacher holds two main tasks, namely teaching and classroom management. Teachers as professional educators have a very complex role, not limited to learning activities, teachers also serve as administrators, evaluators, counselors. Management is an art of getting everything done through other people. A good learning process will minimize the possibility of failures and mistakes in learning. It is important for teachers to have the ability to create good teaching and learning conditions and to achieve optimal levels of effectiveness in instructional activities for classroom management skills.The purpose of this research is to prove whether or not there is a relationship between structuring student learning situations and learning outcomes of Islamic education. To achieve the research objectives, a quantitative approach with correlation is used. To obtain accurate research information, the research instrument used was a checklist scale and a document on student learning outcomes. Then the data obtained were analyzed using statistical analysis and product moment formula. The results of this study explain 5% of 0.250 from a 1% confidence interval of 0.325, with N = 60, and the value of rxy = 1.26. So the results of the research analysis explain that there is a relationship between structuring student learning situations and learning outcomes of Islamic education at MI Nurul Huda Kapongan Situbondo. As for students who use structuring learning situations that are good will get better results than students who do not use structuring learning situations that are not good, of course it will affect the results of these students' learning skills, so that they get unsatisfactory results. Peran guru dalam pengelolaan kelas sangat penting untuk menciptakan suasana pembelajaran yang berkualitas, secara prinsip, guru memegang dua tugas pokok, yakni pengajaran dan pengelolaan kelas. Guru sebagai tenaga pendidik profesional memiliki peran yang sangat kompleks, tidak terbatas pada kegiatan pembelajaran, guru juga bertugas sebagai administrator, evaluator, konselor. Manajemen merupakan suatu seni untuk mendapatkan segala sesuatu dilakukan melalui orang lain. Proses pembelajaran yang baik akan meminimalkan kemungkinan terjadinya kegagalan serta kesalahan dalam pembelajaran. Guru penting memiliki kemampuan menciptakan kondisi belajar mengajar yang baik dan untuk mencapai tingkat efektivitas yang optimal dalam kegiatan instruksional kemampuan pengelolaan kelas. Tujuan dari penelitian ini adalah untuk membuktikan ada atau tidaknya hubungan antara penataan situasi belajar siswa dengan hasil belajar pendidikan Islam. Untuk mencapai tujuan penelitian maka digunakanlah pendekatan kuantitatif dengan korelasi. Untuk memperoleh informasi yang tepat penelitian instrumen penelitian yang digunakan ialah skala ceklis dan dokumen tes hasil belajar siswa. Kemudia data yang diperoleh dianalisis menggunakan analisis statistik dan rumus produk moment. Hasil penelitian ini menjelaskan 5% sebesar 0,250 dari interval kepercayaan 1% sebesar 0,325, dengan N=60, dan nilai rxy = 1,26. Maka dari hasil analisi penelitian menjelaskan terdapat hubungan antara penataan situasi belajar siswa dengan hasil belajar pendidikan Agama Islam di MI Nurul Huda Kapongan Situbondo. Adapun siswa yang menggunakan penataan situasi belajar yang baik akan mendapatkan hasil yang lebih baik dibandingkan dengan siswa yang tidak menggunakan penataan situasi belajar yang tidak baik, tentu akan berpengaruh terhadap hasil kecakapan belajar siswa tersebut, sehingga mendapatkan hasil yang tidak memuaskan.